1999
DOI: 10.1200/jco.1999.17.9.2915
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Chemoradiotherapy for T4 and/or M1 Lymph Node Squamous Cell Carcinoma of the Esophagus

Abstract: Despite its significant toxicity, this combined modality seemed to have curative potential even in cases of locally advanced carcinoma of the esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
355
9
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 404 publications
(396 citation statements)
references
References 16 publications
28
355
9
4
Order By: Relevance
“…However, it should be pointed out that three of them responded to the treatment, one obtained a pCR and another is one of the four long living. These findings are similar to the results reported by Ohtsu et al (1999)) and Polee et al (2003)) and support the concept that chemoradiotherapy has the same curative potential, for locally advanced disease, irrespective of mediastinal or M1a node extension; therefore, separating these groups is not strictly necessary. The utility of surgical resection after chemoradiotherapy in advanced oesophageal cancer is still not established; in spite of this, we offered responding patients the possibility of resection, as this was the best way to ascertain the rate of complete response, and residual tumour resection could be beneficial.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, it should be pointed out that three of them responded to the treatment, one obtained a pCR and another is one of the four long living. These findings are similar to the results reported by Ohtsu et al (1999)) and Polee et al (2003)) and support the concept that chemoradiotherapy has the same curative potential, for locally advanced disease, irrespective of mediastinal or M1a node extension; therefore, separating these groups is not strictly necessary. The utility of surgical resection after chemoradiotherapy in advanced oesophageal cancer is still not established; in spite of this, we offered responding patients the possibility of resection, as this was the best way to ascertain the rate of complete response, and residual tumour resection could be beneficial.…”
Section: Discussionsupporting
confidence: 90%
“…The high percentage of fistulisation observed might be explained by the prevalence of T4 lesions, localised mostly in the upper or middle portion of the oesophagus. The high risk of treatment-related perforation of the oesophageal wall in T4 oesophageal patients was also highlighted by Ohtsu et al (1999). In order to reduce the perforation risk, we decided to use induction chemotherapy, before chemoradiotherapy, with the hope of decreasing the tumour volume before encountering severe oesophagitis and stomatitis.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search produced no other studies that specifically investigated chemoradiotherapy for locally advanced disease, such as T4 and/or M1 LYM. In our previous study, a CR rate of 33% and a 3-year survival rate of 23% were achieved in patients with unresectable T4 tumours and/or M1 LYM disease (Ohtsu et al, 1999), suggesting that concurrent chemoradiotherapy was potentially curative for locally advanced carcinoma. In our present study, a CR rate of 39% and a 3-year survival rate of 19% were achieved in patients with 'severe dysphagia' accompanied by T3 or T4 disease.…”
Section: Discussionmentioning
confidence: 85%
“…In a prospective randomised trial by the Radiation Therapy Oncology Group, which compared chemoradiotherapy with radiotherapy alone, the combined-modality arm demonstrated a significant improvement of survival (Herskovic et al, 1992), with a 5-year survival rate of 27%, compared with 0% for radiotherapy alone (Al-Sarraf et al, 1997). With regard to the indications of chemoradiotherapy as a curative treatment for patients with locally advanced diseases, our multicentre study suggested that concurrent chemoradiotherapy was potentially curative even in cases with locally advanced carcinoma of the oesophagus (i.e., T4 and/or M1 lymph node metastasis (LYM) disease) (Ohtsu et al, 1999). Of the 54 patients in that study, 18 (33%) achieved a complete response, and the 3-year survival rate was 23%.…”
mentioning
confidence: 80%
See 1 more Smart Citation